Constraint handling techniques used with evolutionary algorithms. analysis and applica-tion - Єгорова, Ольга В’ячеславівна (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of evolutionary techniques for constraint satisfaction problem solving is executed.Their advantages and disadvantages have been defined